GRB7-mediated enhancement of cell malignant characteristics induced by Helicobacter pylori infection - Zhao, Huilin; Chen, Si; Bai, Xinfeng; Zhang, Jianhui; Liu, Shuzhen; Sun, Zekun; Cao, Xinying; Wang, Jianping; Zhang, Ying; Li, Boqing; Ji, Xiaofei (Frontiers in Microbiology, 2024)
Growth factor receptor bound protein 7 (GRB7) is reportedly upregulated in human gastric cancer (GC), which is closely associated with tumor progression and prognosis. However, the mechanism underlying its dysregulation in GC remains poorly understood. In this study, we found that GRB7 overexpression was associated with Helicobacter pylori (H. pylori) infection. GC cells (AGS and MGC-803) infection assays revealed that this upregulation was mediated by the transcription factor STAT3, and activation of STAT3 by H. pylori promoted GRB7 expression in infected GC cells. Moreover, CagA, the key virulence factor of H. pylori, was found involved in STAT3-mediated GRB7 overexpression. The overexpressed GRB7 further promoted GC cell proliferation, migration, and invasion by activating ERK signaling. Mice infection was further used to investigate the action of GRB7. In H. pylori infection, GRB7 expression in mice gastric mucosa was elevated, and higher STAT3 and ERK activation were also detected. These results revealed GRB7-mediated pathogenesis in H. pylori infection, in which H. pylori activates STAT3, leading to increased GRB7 expression, then promotes activation of the ERK signal, and finally enhances malignant properties of infected cells. Our findings elucidate the role of GRB7 in H. pylori-induced gastric disorders, offering new prospects for the treatment and prevention of H. pylori-associated gastric carcinogenesis by targeting GRB7.